Attitude and Bias towards the Standard Varieties of Galician and Spanish Language in an Educational Setting - Iglesias Álvarez, Ana (Madrygal. Revista de Estudios Gallegos, 2020)
This paper focuses on the last phase in the standardising process of Galician language, and particularly on its implementation by one of its major agents, language teachers. For that purpose, we carried out a closed-question survey about teachers’ perception on students’ knowledge of Galician and Castilian languages and their appreciation for them. Teachers were asked to assess their pupils’ linguistic knowledge, and to give their opinion about their students’ self-assessment. This information was used to analyse the possible bias related to the perception of the standard variety in the educational settings and its impact in the social image of both languages. As this article belongs to a larger research project –in which the student’s own perspective is also taken into account, through qualitative techniques–, the paper also offers a comparison and contrast of teachers’ and students’ results.